Experimental study on rock fracture toughness under temperature and confining pressure coupling condition - Bo Cai; Nailing Xiu; Dongxu Li; Haifeng Fu; Xiaodong Dai; Dawei Deng; Hexiang Zhao; Xueyuan Han; Songyang Yuan; Liangang Deng (Frontiers in Earth Science)
The fracture toughness is an essential mechanical parameter to measure the difficulty of hydraulic fracture expansion. As the reservoir depth increases, the temperature and stress become higher. In particular, the high-temperature and high-pressure characteristics of the 10,000-m-deep reservoir are particularly pronounced. Furthermore, investigating the fracture toughness evolution under such coupled thermomechanical conditions serves as a critical focus of ultra-deep reservoir studies, providing essential insights for optimizing hydraulic fracturing designs. This study investigates the coupled effects of temperature and confining pressure on the fracture toughness of carbonate rocks through systematic experimental and theoretical analyses. Utilizing outcrop samples from the Cambrian Sholbrak Formation (analogous to the 10,000-m-deep target layer of the Ke exploration well), fracture toughness tests were conducted under thermomechanical coupling conditions (25°C–200°C, 0–200 MPa) via the double-wing symmetric crack thick-wall cylinder method implemented on a GCTS high-temperature/high-pressure rock mechanics system. Key findings reveal a temperature-dependent degradation of fracture toughness (40% reduction from 25°C to 200°C at zero confining pressure) and a confining pressure-driven enhancement (76% increase from 0 to 100 MPa at ambient temperature). A damage mechanics-based constitutive model was developed to quantify these dual effects, demonstrating strong agreement with experimental data (mean absolute error <5%). This model addresses the critical gap in fracture toughness characterization under deep reservoir conditions, enabling enhanced accuracy in hydraulic fracture propagation simulations for ultra-deep carbonate reservoir stimulation.